Studi etnomedisinal masyarakat Melayu di Kabupaten Tanjung Jabung Barat, Jambi - Siti Susiarti; F.M. Setyowati; J. J. Afriastini (Journal of Tropical Ethnobiology, 2005)
Study on the Etnomedicinal of Malay society was carried out in the concession area of HTI PT Wirakarya Sakti. This study is a part of a valuation on Non Timber Forest Products (NTFPS) which has been started since 2003. The method employed in this study is "sampling ethno-direct' and it perceives various aspects related to traditional medication technique which exploits the diversity of plants as ingredient. The result of this study is noted 77 plant species known as a traditional medicine. Qualitative analysis on chemical content indicates that some of those species have a potency to be analyzed further on their useful and benefit. This study has also noted the technique existence of adaptation change developed by society in order to response the happening of environmental change in the area. Under the above condition this study is one of the efforts to document a local wisdom and knowledge on medication technique by using plant diversity as a drug ingredient.